INTANGIBLE CULTURAL HERITAGE IN CENTRAL ASIAN COUNTRIES AND CHINA: SILK ROAD CONNECTIVITY AND CULTURAL VALUE CONNOTATION - YI ZHAO; TONGQIAN ZOU; XINGYU FENG; Albattat, Ahmad; YIDING WANG (International Journal of Multidisciplinary Research and Studies, 2023)
The Silk Road has been an important link between East and West throughout history, facilitating cultural exchanges and commercial interchange between Asia and Europe and developing civilizations in many nations. With their unique history, culture, and geographic relationship with several surrounding countries, Central Asia has always been critical to the Silk Road. They not only supply East-West transportation but also have a rich and spectacular history and culture. This article examines the visible cultural heritage of Central Asian countries through the "Silk Road," its reflection, and the soft cultural relationship between them and our country via connotation. This article will analyze how tangible cultural legacy depicts the history and culture of the eras and places in which it is found, as well as how essential it will be to future generations, using case studies. The cultural connectivity of the Silk Road as a valuable bridge will be linked through extensive case studies and major conversations on cultural values. China and Central Asian countries have been able to further consolidate consensus, strengthen cooperation, and move toward the path of a common and prosperous civilization by realizing the diversity and richness of civilizations and promoting the prosperity and development of human civilization through exchanges and cooperation in tangible cultural heritage.